(untitled) (The New Uzbekistan Journal of Medicine, 2025)
The article discusses the helminths that are dangerous for the human body - nematodes (roundworms) worms), trematodes (flukes) and cestodes (tapeworms) classes and their main parasitic species, their disease-causing properties and measures to combat them are covered.